Regulation of neuroblast mitosis is determined by PACAP receptor isoform expression - Nicot, Arnaud (National Academy of Sciences, 2001)
Although neurogenesis in the embryo proceeds in a region- or lineage-specific fashion coincident with neuropeptide expression, a regulatory role for G protein-coupled receptors (GPCR) remains undefined. Pituitary adenylate cyclase activating polypeptide (PACAP) stimulates sympathetic neuroblast proliferation, whereas the peptide inhibits embryonic cortical precursor mitosis. Here, by using ectopic expression strategies, we show that the opposing mitogenic effects of PACAP are determined by expression of PACAP receptor splice isoforms and differential coupling to the phospholipase C (PLC) pathway, as opposed to differences in cellular context. In embryonic day 14 (E14) cortical precursors transfected with the hop receptor variant, but not cells transfected with the short variant, PACAP activates the PLC pathway, increasing intracellular calcium and eliciting translocation of protein kinase C. Ectopic expression of the hop variant in cortical neuroblasts transforms the antimitotic effect of PACAP into a promitogenic signal. Furthermore, PACAP promitogenic effects required PLC pathway function indicated by antagonist U-73122 studies in hop-transfected cortical cells and native sympathetic neuroblasts. These observations highlight the critical role of lineage-specific expression of GPCR variants in determining mitogenic signaling in neural precursors.